STUDY ON THE ANTIBACTERIAL ACTIVITY OF FRUIT EXTRACTS OF KLUTUK BANANA (MUSA BALBISIANA COLLA) AGAINST SHIGELLA DYSENTERIAE ATCC 13313 - Kusuma, Sriagung Fitri; Mita, Soraya R; Firdayani, Indah; Mustarichie, Resmi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this study is to determine the antibacterial activity of Klutuk Banana (Musa balbisiana colla) fruit extracts against Shigella dysenteriae ATCC 13313 and the amount of potassium to the discovery of anti-dysentery drug candidates. Methods: The simplisia of Klutuk banana fruit was extracted with ethanol using a maceration method. The phytochemical screening of ethanol extract was performed using standard procedures. Determination thin layer chromatography (TLC) profile of the extract was performed using a thin layer plate. The antibacterial activity was investigated using agar well diffusion technique. The minimum inhibitory concentrations (MIC) were determined by a serial microdilution method, whereas the minimum bactericidal concentration (MBC) was done by subculturing the MIC result onto agar medium. Potassium levels of the extract were carried out quantitatively using atomic absorption spectrophotometry. Results: The phytochemical analysis revealed the presence of flavonoids, polyphenols, tannins, monoterpenoid and sesquiterpenoids, quinones, and saponins. The TLC results prove the existence of flavonoids in the tested extract. The content of secondary metabolites that can act as an antibacterial, strengthen the antibacterial activity of ethanol extract of Klutuk banana against S. dysenteriae 13313 with MBC values in the range of 5-10%w/v. Potassium levels in the ethanol extract of Klutuk banana fruits contain potassium as much as 2.919% (29 190 ppm). Conclusion: It can be concluded that the ethanol extract of Klutuk banana fruits is more potent as antibacterial against S. dysenteriae than as potassium supplier in hypokalemia therapy.